LEGAL ANALYSIS OF CRIMINAL ACTS BY PERPETRATORS ON SOCIAL MEDIA BY INTENTIONALLY ACCESSING ELECTRONIC INFORMATION / ELECTRONIC DOCUMENTS CONTAINING INSULTING / DEFAMATION (STUDY OF DECISION NUMBER 5201 K/Pid.Sus/2025/PN. Lubuk Pakam) - Wahyu Utama Putra Nasution; Rahmayanti (PT. Radja Intercontinental Publishing, 2026)
The existence and use of the internet today is like a double-edged sword. Besides contributing to the improvement of human welfare and the advancement of civilization, it can also be a means for committing various unlawful acts, including criminal acts. These crimes include information espionage, data theft, credit card fraud, the spread of computer viruses, adult and child pornography, the distribution of problematic emails, and anti-ethnic, religious, racial, and intergroup (SARA) campaigns, terrorism, and extremism via the internet. These various forms of crime are known as